Changes in biomechanical knee injury risk factors across two collegiate soccer seasons using the 11+ prevention program - Arundale, A. J. H.; Silvers-Granelli, H. J.; Marmon, A.; Zarzycki, R.; Dix, C.; Snyder-Mackler, L. (Scandinavian Journal of Medicine & Science in Sports, 2018)
The 11+ injury prevention program effectively reduces injuries in high school aged female soccer player, but the mechanism of the 11+ is unknown, particularly whether it impacts biomechanical risk factors associated with knee injuries. The purpose was to report the changes in hip and knee biomechanics with use of the 11+ over two soccer seasons. Two collegiate women's soccer teams performed the 11+ for two soccer seasons. A control team was followed for one season. Athletes performed motion analysis of a drop vertical jump during preseason and postseason. Both groups had meaningful increases in peak knee abduction angle over the first season, and there were no meaningful changes in peak knee abduction moment over either season. The control group had bilateral decreases in knee flexion angle. The program did not seem to systematically impact biomechanical risk factors associated with knee injuries, with increase in peak knee abduction angle no bilateral changes in frontal or transverse hip motion. The 11+ may have mitigated clinically meaningful decreases in knee flexion, however as ACL injuries do not occur purely in the sagittal plane, it is unclear the impact of these changes. The results of this study indicate that the 11+ may require some modifications to impact landing biomechanics and potentially risky movement patterns, particularly when used in collegiate women over multiple seasons.